Biomarkers associated with early stages of kidney disease in adolescents with type 1 diabetes. Issue 7 (17th August 2020) - Marcovecchio, Maria Loredana; Colombo, Marco; Dalton, Raymond Neil; McKeigue, Paul M.; Benitez‐Aguirre, Paul; Cameron, Fergus J.; Chiesa, Scott T.; Couper, Jennifer J.; Craig, Maria E.; Daneman, Denis; Davis, Elizabeth A.; Deanfield, John E.; et al.
Abstract: Objectives: To identify biomarkers of renal disease in adolescents with type 1 diabetes (T1D) and to compare findings in adults with T1D. Methods: Twenty‐five serum biomarkers were measured, using a Luminex platform, in 553 adolescents (median [interquartile range] age: 13.9 [12.6, 15.2] years), recruited to the Adolescent Type 1 Diabetes Cardio‐Renal Intervention Trial. Associations with baseline and final estimated glomerular filtration rate (eGFR), rapid decliner and rapid increaser phenotypes (eGFR slopes <−3 and > 3 mL/min/1.73m 2 /year, respectively), and albumin‐creatinine ratio (ACR) were assessed. Results were also compared with those obtained in 859 adults (age: 55.5 [46.1, 64.4) years) from the Scottish Diabetes Research Network Type 1 Bioresource. Results: In the adolescent cohort, baseline eGFR was negatively associated with trefoil factor‐3, cystatin C, and beta‐2 microglobulin (B2M) (B coefficient[95%CI]: −0.19 [−0.27, −0.12], P = 7.0 × 10 −7 ; −0.18 [−0.26, −0.11], P = 5.1 × 10 −6 ; −0.12 [−0.20, −0.05], P = 1.6 × 10 −3 ), in addition to clinical covariates. Final eGFR was negatively associated with osteopontin (−0.21 [−0.28, −0.14], P = 2.3 × 10 −8 ) and cystatin C (−0.16 [−0.22, −0.09], P = 1.6 × 10 −6 ). Rapid decliner phenotype was associated with osteopontin (OR: 1.83 [1.42, 2.41], P = 7.3 × 10 −6 ), whereas rapid increaser phenotype was associated with fibroblast growth factor‐23 (FGF‐23) (1.59 [1.23, 2.04], P = 2.6 × 10 −4 ). ACR was not associated with any of the biomarkers. In the adult cohort similar associations with eGFR were found; however, several additional biomarkers were associated with eGFR and ACR. Conclusions: In this young population with T1D and high rates of hyperfiltration, osteopontin was the most consistent biomarker associated with prospective changes in eGFR. FGF‐23 was associated with eGFR increases, whereas trefoil factor‐3, cystatin C, and B2M were associated with baseline eGFR.